Tutkimus- ja kehitystoiminnan kansainvälistyminen; The Internationalization of R&D - Jyrki Ali-Yrkkö; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2019)
– The aim of this paper is to broaden the knowledge concerning the development of Finnish firms' innovation activities. The results show that during 2008–2017 the share of overseas R&D has risen. Currently, 14–25% of Finnish firms' total R&D are conducted overseas. If Nokia is taken into account, the share of overseas R&D rises to 53–65%. Furthermore, the results suggest that Finnish firms invest approximately Eur 1.8 billion in innovation activities outside the traditional R&D definition.
Keywords: O31; O32; 330; Research; Development; R&D; Company; BERD; Internationalization; Globalisation; Innovation; Finnland